Preliminary efficacy of a daily living skills intervention for adolescents with high-functioning autism spectrum disorder. (November 2018) - Duncan, Amie; Ruble, Lisa A; Meinzen-Derr, Jareen; Thomas, Carrie; Stark, Lori J
Daily living skills deficits are strongly associated with poor adult outcomes for individuals with high-functioning autism spectrum disorder, and yet, there are no group interventions targeting daily living skills. Seven adolescents with autism spectrum disorder and their parents participated in a feasibility pilot of a 12-week manualized group treatment targeting specific daily living skills (i.e. morning routine, cooking, laundry, and money management). Outcomes included the Vineland Adaptive Behavior Scales, Second Edition (Vineland-II) age equivalence scores and four goal attainment scaling scores. Adolescents demonstrated significant improvement on two Vineland-II subdomains and on all goal attainment scaling scores at post-treatment and 6-month follow-up. The intervention has promise for improving critical daily living skills' deficits that affect independent living and employment. Limitations and implications for future studies are discussed.